Anemia In Pregnancy: Risk Factors, Impacts, And Prevention Efforts - Adriana Bangun; Chandra Juita Pasaribu; Ratih Widya Wati Gultom; Zahra Tri Utami; Anggi Putri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to analyze current evidence on the prevalence, risk factors, clinical impacts, and prevention strategies of anemia during pregnancy. Anemia in pregnancy remains a critical global health issue, particularly in low- and middle-income countries, where it contributes substantially to maternal and perinatal morbidity and mortality. The condition is primarily caused by iron deficiency, but folate, vitamin B12 deficiencies, infections, and socio-economic inequalities also play pivotal roles. This review aims to synthesize existing research on the biological, nutritional, and socio-economic determinants of anemia in pregnancy and evaluate their implications for maternal and fetal health. A systematic literature review was conducted using electronic databases such as PubMed, ScienceDirect, Scopus, and Google Scholar, covering studies published between 2015 and 2024. Keywords included “anemia in pregnancy,” “iron deficiency,” “maternal and fetal health,” “nutritional risk factors,” and “socio-economic determinants.” Inclusion criteria encompassed peer-reviewed studies written in English focusing on anemia in pregnant women. Data were analyzed thematically according to clinical impacts, nutritional causes, and preventive strategies. The findings reveal that maternal anemia significantly increases the risk of postpartum hemorrhage, preterm birth, low birth weight, and intrauterine growth restriction. Iron deficiency remains the predominant cause, exacerbated by inadequate dietary intake and poor supplement adherence. Socio-economic variables such as low education, poverty, and limited healthcare access further elevate anemia risk. Preventive interventions iron-folic acid supplementation, dietary diversification, and community education—were found effective but variably implemented. Anemia in pregnancy is a multifactorial condition requiring integrated medical, nutritional, and socio-economic interventions. Strengthening antenatal care systems, improving women’s education, and promoting nutritional programs are essential for sustainable prevention. Comprehensive approaches addressing both clinical and social determinants are crucial for reducing anemia-related maternal and fetal complications.